Mobility as a Service - an open ecosystem? - Sørensen, Søren (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
Can we get public transit and private shared mobility providers to deliver multimodal shared mobility services within months rather than year simply by using MaaS. The technology is there but the major obstacles are governance and will power. Is the only solution the Finnish model: Open MaaS by lawmaking - the stick? – or is there a carrot way too? The incumbent mobility suppliers are used to “own” their customers and does not necessarily see the benefits of having an extra part (The MaaS agent) in the value chain between them and “their” customers. The necessity for the shared mobility actors to come together to present a compelling alternative to the private car is presented and discussed. To create a level playing field for a shared mobility ecosystem including MaaS, a set of rules of engagement or charter is needed. An example is introduced as the carrot method or MaaS as common business sense.